Exploratory Study on Kali NetHunter Lite: A Digital Forensics Approach - Miloš Stanković; Umit Karabiyik (Journal of Cybersecurity and Privacy, 2022)
Mobile devices, specifically smartphones, have become a necessity in everyday life, as we perform many essential day-to-day tasks using these devices. With the projected increase in mobile devices to 18.22 billion by 2025, the reliance on smartphones will only grow. This demand for smartphones has allowed various companies to start developing their own devices and custom operating systems, each of which puts its own touch on them. In addition, current smartphones have increased processing power, providing users with a computer experience in their pockets. Software developers have taken this opportunity to bridge the gap between personal computers and smartphones by creating the same software for personal computers and mobile devices. Kali Linux is one of the most popular penetration testing tools for desktop use and has been adapted to operate on mobile devices under the name Kali NetHunter. Kali NetHunter has three different versions on mobile platforms that provide various levels of capabilities. Kali NetHunter is just one example in which an application or an operating system applies to a specific niche of users. Highly customized operating systems or applications do not receive the same attention as field research, leaving them unfamiliar to mobile forensic investigators when used maliciously. In this paper, we conducted an exploratory study on the Kali NetHunter Lite application after it was installed and its embedded tools were utilized. Our results show a detailed analysis of the file system and reveal the data from the tests carried out during various phases. Furthermore, the locations of the folders involved in the process were described.